The influence of H2 and NH3 on catalyst nanoparticle formation and carbon nanotube growth. (December 2020) - Pezone, R.; Vollebregt, S.; Sarro, P.M.; Unnikrishnan, S.
Abstract: Control of the morphology of carbon nanotubes (CNT) is fundamental for many applications. It is known that the catalyst distributions influence the vertical alignment and the height of the CNT. In this work we investigate the influence of the pre-anneal time and reductant gases, specifically NH3 and H2 as well as combinations thereof, on the nanoparticle (NP) formation and CNT growth. The gases H2, NH3 show opposite roles during the dewetting of 1 nm Fe catalyst layer. The H2 favours uniform NP distributions (mean diameter of 15 nm) and the NH3 forms large clusters. Playing with double annealing steps H2 - NH3 we obtained NP with larger mean diameters μ = 20 nm. We observed a mismatch between the diameters of the NP directly after annealing and the CNT after growth, due to a reshaping of the catalyst NP before the CNT nucleation. Furthermore, we found that longer annealing times decrease the CNT forest height and the H2 exposure during the annealing improves the height and the alignment of the CNT. Graphical abstract: Image 1